Mobile Learning Application Impact Towards Student Performance in Programming Subject - Farahah Abdul Halim, Nurul; Nincarean Eh Phon, Danakorn (IOP conference series. Materials Science and Engineering, 2020)
Writing a program is significant basic proficiency for computer science students. However, majority of the students found it is difficult to learn and score a high mark. In an era of rapidly changing technologies, mobile learning has received increasing emphasis and widely used among educational practitioners and researchers. Thus, the objective of this study is to investigate the factors that influence students learning performance and evaluate the effectiveness of mobile learning using Learn C application in Programming subject. Prior to the factors that influence students learning outcome, a survey was conducted with 88 first year undergraduate students from Faculty of Computer Systems & Software Engineering. Next, a pre-experimental one group pretest-posttest research design was employed with 17 students as respondents to examine the impact of mobile learning application. The collected data was then analysed using thematic analysis, descriptive and inferential statistics. The results showed that there are several factors that affect students learning performance in programming that is, misunderstanding, lack of practices, poor logical thinking and problem solving, no prior knowledge, psychological disorder, less interest, ineffective teaching method and bad attitude. The paired sample t-test of student's pre-test and post-test scores demonstrate that there were no significant differences before and after the treatment through mobile learning application given. The study has gone some way in enhancing our understanding of factors that affect student in programming learning which could be used to facilitate the development of the students programming abilities.